2011
DOI: 10.2118/136870-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Optimization of Catalytic Process In Situ for Heavy-Oil and Bitumen Upgrading

Abstract: Summary The worldwide conventional crude-oil demand is on the rise, and because of the rising prices, unconventional oils are becoming more economically attractive to extract and refine. However, technological innovation is needed if heavier oil supplies are to be exploited further. Toe-to-heel air injection (THAI) and its catalytic add-on processes (CAPRI) combine in-situ combustion with catalytic upgrading using an annular catalyst packed around the horizontal producer well. These techniques o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 14 publications
(15 reference statements)
0
30
0
Order By: Relevance
“…The prospect of the THAI-CAPRI process to produce partially upgraded oil has been proven in simulation, laboratory and field trials [3][4][5][6][7][8][9][10][11][12][13][14]. The comparison of Kerrobert field THAI and SAGD projects showed that, though the THAI peak oil production rate (0.06 m 3 day −1 m −1 ) was lower than SAGD (0.3 m 3 day −1 m −1 ), the produced oil with THAI was moderately upgraded by 5 • points API gravity increase, whereas that of SAGD showed negligible upgrading [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prospect of the THAI-CAPRI process to produce partially upgraded oil has been proven in simulation, laboratory and field trials [3][4][5][6][7][8][9][10][11][12][13][14]. The comparison of Kerrobert field THAI and SAGD projects showed that, though the THAI peak oil production rate (0.06 m 3 day −1 m −1 ) was lower than SAGD (0.3 m 3 day −1 m −1 ), the produced oil with THAI was moderately upgraded by 5 • points API gravity increase, whereas that of SAGD showed negligible upgrading [4].…”
Section: Introductionmentioning
confidence: 99%
“…These ranges of temperatures are inadequate to produce significant catalytic upgrading in the hot oil as it flows over the catalyst packing. On the contrary, a temperature of 425 • C has proven to be the optimum from laboratory-scale investigations [6,8,9]. This study therefore focusses on the incorporation of an induction heating coil to the horizontal production well of the THAI-CAPRI process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations